169k views
3 votes
Pleaseeeeeeeeeee help me! Thank you!

Pleaseeeeeeeeeee help me! Thank you!-example-1
Pleaseeeeeeeeeee help me! Thank you!-example-1
Pleaseeeeeeeeeee help me! Thank you!-example-2

2 Answers

4 votes

Answer:

Explanation:

The other responder works better with Latex than I do. I would have been too late anyway.

f(t) = 50*(1/2)^(t - 2)/5

f(t) = 50*(1/2)^(t/5) * (1/2)^(-2/5)

f(t) = 50* (1/2)^t/5 / (1/2)^(2/5)

f(t) = 50*
\frac{\sqrt[5]{((1)/(2))^t}}{((1)/(2))^(2)/(5) }

User Pfa
by
6.0k points
4 votes
Answer:

The correct answer is D.

Explanation:

The given expression for the substance in shipment 2 is


f(t)=50((1)/(2))^{(t-2)/(5)}


f(t)=50((1)/(2))^{((t)/(5)-(2)/(5))}

We use the law of exponents to determine an equivalent expression.

Recall that,


a^(m-n)=\frac{a^m} {a^n}

We apply this property to obtain,


f(t)=\frac{50((1)/(2))^{(t)/(5)}}{((1)/(2))^{(2)/(5)}}

The correct answer is D